Composite construction in steel and concrete VII : proceedings of the 2013 International Conference on Composite Construction in Steel and Concrete, July 28-31, 2013, North Queensland, Australia - Bradford, M. A., 1955-; Uy, Brian (American Society of Civil Engineers, 2016)
This collection contains 59 peer-reviewed papers on a wide variety of composite construction topics presented at the International Composite Construction in Steel and Concrete conference, held in Palm Cove, North Queensland, Australia, July 28-31, 2013.